In silico analysis of the structure of variable domains of mouse single-chain antibodies specific to the human recombinant interferon β1b - Flyak, A.I.; Pavlova, M.V.; Gilchuk, P.V. (Цитология и генетика, 2009)
In silico analysis of the DNA encoding singlechain Fv antibodies (ScFv) specific to the human recombinant interferon β1b and α2b (rhIFNβ1b, rhIFNα2b) has been carried out. The V, D and J-gene segments, the complementaritydetermining (CDR) and framework (FR) regions, n-nucleotides as well as mutation rates which take place during the affinity maturation of the examined sequences have been determined. For the panel of ScFv against rhIFNβ1b isolated from an immune combinatorial cDNA library uniqueness of the CDRH3 loop by the length and amino acid composition has been shown. Multiple alignments with the nearest homologies from the NCBI databases have revealed that the sequences of ScFv obtained are new. Проведен in silico анализ структуры последовательностей ДНК, кодирующих специфические к интерферону β1b и α2b человека (rhIFN β1b, rhIFN α2b) одноцепочечные антитела (ScFv – single chain Fv): определены V, D и J сегменты, границы антиген связывающих (CDR) и каркасных (FR) участков, n нуклеотиды, а также величина мутационных процессов, которые имели место при аффинном дозревании последовательностей in vivo. Для представителей панели ScFv против rhIFN β1b, изолированных из иммунной комбинаторной библиотеки кДНК V генов, показана уникальность участка CDRH3 как по длине, так и по аминокислотному составу. Множественное выравнивание с ближайшими гомологами базы данных NCBI показало, что полученные нами последовательности ScFv являются новыми. Проведено in silico аналіз структури послідовностей ДНК, які кодують специфічні до рекомбінантного інтерферону β1b та α2b людини (rhIFN β1b, rhIFN-α2b) одноланцюгові антитіла (ScFv – single chain Fv): визначено V , D та J генні сегменти, межі антигензв’язувальних (CDR) та каркасних (FR) ділянок, n- нуклеотиди, а також величину мутаційних процесів, що мали місце при афінному дозріванні даних послідовностей in vivo. Для представників панелі ScFv проти rhIFN β1b, ізольованих з імунної комбінаторної бібліотеки кДНК V генів, показано унікальність ділянки CDRH3 як за довжиною, так і за амінокислотним складом. Множинне вирівнювання з найближчими гомологами бази даних NCBI показало, що одержані нами послідовності ScFv є новими.